The Political Elite of the United Development Party in Conducting Political Propagation in Gowa Regency - Muh Fajar; Abdul Halik; Kamaluddin Tajibu (Jurnal Mercusuar, 2022)
Siyasah preaching is one of the various types of preaching institutionalized with a mission in Islam. Political preaching, commonly referred to as siyasah preaching or structural preaching, and political power are utilized as instruments aimed at upholding Islam. The main issues in this research are how the political elites of the United Development Party (PPP) carry out siyasah preaching in Gowa Regency, and how the legislative members of the PPP Faction build the party's image in Gowa Regency. This research employs a qualitative descriptive approach with a phenomenological and preaching approach. The data collection methods involve observation, interviews, and documentation. The data processing and analysis techniques encompass three stages: data reduction, data display, and drawing conclusions. The results of this study indicate that: First, the political elites of the United Development Party (PPP) conduct siyasah preaching in Gowa Regency by providing aspiration houses for the entire Gowa community, engaging in active and continuous political communication with the executive and other parties, lobbying and negotiating with the executive and other parties, recruiting cadres in line with the party's vision and mission, and carrying out cultural preaching. Second, legislative members of the PPP Faction build the party's image in Gowa Regency by providing social assistance to the community, not only during campaign seasons but also continuously. They follow up on every community aspiration, work collectively and collegially within the PPP Faction, and assist the community in various aspects, including the smallest matters. The implications of this research include: (1) The management of the United Development Party in Gowa Regency needs to evaluate the PPP Faction members and DPRD every month and conduct community visits not only for DPRD members but also for party executives. (2) Training for the members of the PPP Faction in the DPRD to prioritize the interests of the community across different electoral districts. (3) Party elites and members of the PPP Faction in the DPRD should maintain internal party communication and communicate with other parties to realize a just and prosperous society.